Architecture of Cossack settlements in the 16th–18th centuries - Ponomarenko, Elena V. (Opción, 2019)
The research objective is to show how Cossacks’ early settlements emerged and their architectural development shaped itself in the Middle Volga and South Urals. The methodology of the study is based on a comprehensive architectural historical analysis of the layouts, composition and character of early Cossack settlements in the region in the 16th – 18th centuries. In result, in the aspect of historical development, the process of formation of architectural and town-planning heritage of Cossacks may be represented as a series of an artificial environment’s distinct states. In conclusion, the most significant element in the fortress-settlement composition was the fortress itself.